Prevalence of Anxiety Disorders Among Adolescents: A Cross-Sectional Study in An Urban Area of Delhi, India - Febida BPK; Akshithanand KJ; Rajesh Kumar; Panna Lal; Bratati Banerjee (National Journal of Community Medicine)
Background: Adolescence is a critical period and anxiety disorders affect one in seven adolescents globally, yet data on this in the Indian population remain limited. This research aimed to study the prevalence and types of anxiety disorders among adolescents in an urban area of Delhi.